Training on production of liquid organic fertilizer for family welfare development (PKK) Group in Matesih Village, Karanganyar, Central Java - Santhyami Santhyami; Difa Hasna Febriyanti; Tamia Salsha Novita; Anggraeni Ayu Puspitaning Winhar (Universitas Muhammadiyah Magelang, 2022)
Waste problem is considered as the global issue. Many areas are still facing difficulty in managing waste due to the lack of knowledge especially in waste recycling. Household waste is a common problem experienced by the Matesih Village community, Karanganyar, Central Java. This community service aims to raise awareness of the community about the importance of household waste recycling and to train them in processing the household waste into the liquid organic fertilizer (LOF). The target of this community service was 10 women of Family Welfare Development (PKK) community. The methods used in this activity were transfer of knowledge and demonstrating. This training produced 16.7 liter of LOF with average pH of 6. Based on the survey, participants were satisfied with the socialization and training activities and willing to continue the program of making LOF independently.